Polychronicity: Model and analysis of conditional process toward employee turnover intentions - Rian Andriani; Disman Disman; Eeng Ahman; Budi Santoso (Journal of Innovation in Business and Economics, 2021)
The hospitality industry in Indonesia is growing rapidly but lagging behind the readiness of human resources. The hotel industry has a crucial problem of retaining employees where there is a gap between the interests of employees and the interests of the company. Turnover intention is the main predictor of turnover, so aspects that can affect turnover intention will affect turnover. This study aims to describe and analyze the relationships between variables and dimensions in the research model or paradigm developed by the researcher. It tested the conditional process model using path analysis based on OLS regression and bootstrap methods. The population in this study were employees of the hotel industry in Indonesia, with a sample of 257 employees. The findings of this study are that the work environment has no direct effect on the variables of job satisfaction, employee engagement, and turnover intention but can interact as a moderator variable so that it effectively moderates the impact of polychronic on turnover intention through full mediation of job satisfaction and employee engagement.